Estudo da secagem de resíduos de acerola em tambor rotativo acoplado a micro-ondas - Ramadan, Lina (2017)
Fruit growing is an important segment of Brazilian agribusiness. Approximately 53% of the production are marketed as fresh fruit and 47% are intended to produce juices, jams and jellies in manufacturing industries. Brazil is among the largest producers of fruits, including acerola, which is rich in vitamins and antioxidants. Fruit processing generates annually tons of residues that normally do not have proper disposal. Reusing agri-industrial residues avoids negative impacts on environment and enables antioxidant compounds acquisition, which can be applied in food and pharmaceutical industries. However, this material has high moisture content that turns its handing more difficult and reduces product life. Dehydration is a unit operation that involves heat and mass transfer and may be applied to reduce moisture content to a level that prevents microbial proliferation and allows the reuse of bioactive compounds. The microwave drying method has been widely utilized due to reduced process time and energy consumption. However, because of uneven heating, association with another dryer that provides motion of particles is an option that may result in process improvements. Therefore a system composed by microwave associated to rotating drum was designed at FEQUI / UFU in order to take advantage of heating efficiency by microwave and stirring provided by rotating drum. The aim is to evaluate the efficiency of the system in homogeneity and drying acerola residue. Firstly, mixing was studied at different conditions of rotational speed, fill degree and residue moisture, through the evaluation of the transient behavior of the segregation index. It was found that high speeds and low fill degrees favored the process. In addition, moisture variation did not significantly influence the results. Subsequently, samples were submitted to microwave associated to rotating drum drying, and the final product was analyzed in terms of removal moisture and bioactive compounds concentration (phenolic, flavonoids and ascorbic acid). An experimental design (3K) was proposed varying rotation speed and microwave power. Fill degree was set at 13%. Higher concentrations of antioxidant compounds were obtained at high speeds (30 and 45 rpm) and microwave power of 300 W. A Central Composite Planning was structured to analyze the effect of fill degree and rotation speed at 300 W. Again, higher levels of bioactive compounds were obtained at high speeds and low and intermediate fill degree. Practically in all cases bioactive compounds concentration of samples after drying were above of the residue in natura. Therefore, results showed interesting performance of the new equipment in the moisture removal and final product quality, presenting a viable method to be applied in drying processes. Thus, rotating drum contributes to heterogeneity reduction, a characteristic pointed in literature as a limiting in microwave drying.